First Identification and genomic characterization of multidrug-resistant carbapenemase-producing Enterobacteriaceae clinical isolates in Malawi, Africa. Issue 12 (29th October 2019) - Kumwenda, Geoffrey P.; Sugawara, Yo; Abe, Ryuichiro; Akeda, Yukihiro; Kasambara, Watipaso; Chizani, Kenneth; Takeuchi, Dan; Sakamoto, Noriko; Tomono, Kazunori; Hamada, Shigeyuki
Abstract : Purpose . Carbapenemase-producing Enterobacteriaceae (CPE) have become a global concern and a serious threat to human health due to their resistance to multiple antibiotics. In this study, we identified and characterized CPE for the first time in Malawi, southeastern Africa. Methodology . We investigated the possible presence of carbapenemases among a collection of 200 ceftriaxone-nonsusceptible Gram-negative clinical isolates obtained from five Malawian hospitals between January 2016 and December 2017, using both phenotypic and genotypic tests. Molecular typing of CPE was done by PFGE, multilocus sequence typing (ST) or phylogenetic grouping. Resistant plasmids were characterized by S1 PFGE, Southern blotting and conjugation assays. Results . Out of 200 isolates, we detected 16 (8 %) CPE of which all originated from one referral hospital, Kamuzu Central Hospital, in the Central part of Malawi. Of 16 isolates, seven Klebsiella pneumoniae ST340/CC258 carried bla KPC-2, two Escherichia coli ST636 (phylogroup B2) carried bla NDM-5, six E. coli ST617 (phylogroup A) and one Klebsiella variicola carried bla OXA-48 . All carbapenemases were plasmid-encoded, but only bla NDM-5 -carrying plasmids could be conjugated. Most isolates co-harboured other β -lactamases and consequently exhibited a wider spectrum of resistance to commonly used antibiotics. We observed indistinguishable genetic profiles between strain types, despite originating from different wards, suggesting acquisition during admission and intra-hospital spread. Conclusion . This report strongly suggests a probable existence of highly resistant various types of CPE organisms in Malawi including KPC-2-producing K. pneumoniae ST340/CC258, a known high-risk epidemic lineage.